Adaption of beans to growing season length in Malawi - National Bean Programme (National Bean Programme, 1990)
Twenty-two bean genotypes were assessed in monoculture and in association with maize (NSCM 41) to identify germplasm genotypes from Bunda, Malawi, that synchronize maturity with the end of the growing season. Responses differed among the 3 trial sites (Ng'onga, Bunda, and Matapwata). In general, yields were lower in association than in monoculture at all sites. Lines Sapelekedwa, 8- 7, 7-8, 6-1, 5-2, 16-6, 2-10, and 11-1 were outstanding considering their high yields in monoculture and in association. Hybrids only performed well in Bunda. Seed size was generally big in Ng'onga; 17 genotypes had seed size between 25-39 g/100 seeds and 3 between 40.8-56.2 g/100 seeds. Genotypes also varied in no. of seeds/pod, with significant differences in Matapwata and highly significant differences in Ng'onga. (CIAT)